Effect of decrease of physical activity on depression and anxiety after the COVID-19 lockdown: A survey study - Kajtna, Tanja; Vučković, Vojko (Frontiers in Psychology, 2022)
Purpose We focused on changes in the amount of physical activity (PA) and depression and anxiety symptoms in people, who were previously regularly physically active, as they were all members of fitness centers at time of lockdown because of COVID-19. Materials and methods We sampled 150 fitness center members, tested individually in facilities of fitness centers. Depression and anxiety were measured with subscales of Personality Assessment Inventory (PAI) and PA was measured with global physical activity questionnaire (GPAQ). Results We found that depression (t = −1.97; p < 0.05) and anxiety (t = −2.66; p < 0.05) was more present in female participants than male participants, single participants experienced more depression (t = 2.04; p < 0.05) than participants in relationship, unemployed participants experienced more depression (F = 3,24; p < 0.05) and anxiety (F = 5,32; p < 0.01) than employed participants and participants with lower levels of education experienced higher levels of affective depression (F = 3,42; p < 0.05) and physiological anxiety (F = 3,72; p < 0.05) than participants with higher levels of education. Finally, we found that mental health can be influenced by changes in amount of movement–both anxiety (p < 0.05) and depression (p < 0.05) (in whole and its specific dimensions) increased for male participants when there is less strenuous work-related activity, less walking, or cycling to work and when they would spend more time each day sitting. For female participants, affective depression (t = 3.78; p < 0.01) and anxiety (t = 3.23; p < 0.01) increased with increased sitting time. Ex-competitive athletes are particularly immune to anxiety (t = −2.18; p < 0.05) and depression (t = −2.09; p < 0.05). Discussion As in some previous studies, our results show that because of lockdown, the most endangered groups for mood disorders are women, singles, unemployed and students, uneducated people and those, who had less PA, and more sitting time. Additionally, those who had some sport competitive history are less endangered for depression and anxiety. Conclusion Isolation has great impact on mental health, the most effective solution to stress relief and anxiety is physical exercise, which was limited or non-existent in the time of pandemic. Ex-professional athletes are especially immune to anxiety and depression in events such as COVID-19 lockdown. For future studies we recommend focusing on likelihood of increased depression and anxiety levels in individuals, who were physically active before the isolation period.